Cytokines profile of mice infected by high and low virulences of Indonesian T. evansi isolates - Dyah Haryuningtyas Sawitri; April Hari Wardhana; Heri Wibowo (Indonesian Center for Animal Research and Development (ICARD), 2017)
Surra in livestock is caused by Trypanosoma evansi, a homoflagella blood protozoa that circulate in extracellular. This disease is widespread in Asia, Africa, South and Central America. According to the immunological aspect, the severity of surra in livestock and mice which infected by trypanosoma is associated with an inflammatory response. On the other hand, the survival time of mice depends on the regulation of Th1 synthesis and proinflammatory cytokines such as IFN-γ and TNF-α. The aim of this study was to observe the responses of proinflammatory cytokines IFN γ, TNF-α and anti-inflammatory IL-10 which result from interaction with parasites. This information is needed for improvements in the management of prevention of Surra in animals. A total of 30 mice were divided into 3 groups. The group was infected with a low virulency T. evansi (Pml287); high virulence (Bang87) respectively and one group was not infected as control. Mice sera were collected in every 4 days for cytokine measurement using an Enzyme Link-Immunosorbent Assay (ELISA). The result showed a difference response of proinflammatory and antiinflammation cytokine profile between the infected mice by isolates Bang 87 and Pml 287. Early deaths in mice infected by Bang 87 isolate were suspected as a result of the response of systemic inflammation syndromes characterized by elevated IFN-γ levels that were not adequately compensated by anti-inflammatory. Anemia contributes to the cause of death in mice that support multiple organ failures (multiple organ disfunction).